ANALISIS YURIDIS TINDAK PIDANA MEMBANTU PEKERJAAN SOSIAL MELALUI MEDIA SOSIAL UNTUK MEMPEROLEH KEUNTUNGAN MATERI (PUTUSAN NOMOR 31/PID.SUS/2021/PN.JKT.UTR): Juridical Analysis of The Crime of Assisting Sexual Work Through Social Media to Obtain Material Benefits (Decision Number 31/Pid.Sus/202/PN.Jkt.Utr) - M. Adit Bastillah Ananta; Andi Widiatno (AMICUS CURIAE, 2024)
Penalties assigned to individuals who engage facilitating sex work via social media, perpetrated by offender, determined on judge in accordance with sanctions applied to defendant who participated aiding sex work through social media for the purpose of gaining material advantages accordance with Article 296 of Criminal Code. This article raises the main issue regarding whether the perpetrators of the crime of assisting sexual work through social media to obtain material gain in accordance with Article 296 of the Criminal Code, and correctly punishment for the crime of assisting sexual work through social media to obtain material gain. This research employs an analytical-descriptive approach under the normative juridical research category. The methodology involves utilizing secondary data from legal resources available in libraries, encompassing both primary legal sources and relevant secondary legal references through library research and qualitative analysis is carried out by drawing conclusions based on deductive logic. The conclusion of this analysis states that the perpetrator's actions are in accordance with Article 296 of the Criminal Code, but there more correctly punishment, Article 27 paragraph (1) ITE can be imposed on defendant because of act committed by defendant using electronic information facilities.